Building sustainable human resource work meaning: A case study of Generation Z - Sukmawati; Suriani, Seri; Karim, Abdul; Setiawan, Lukman; Yunus, Muhammad Kafrawi (International Journal of Management and Sustainability, 2025)
This study explores meaningful work for Generation Z and its impact on employee retention. The study was conducted through an online survey of 310 Generation Z employees in Makassar who were born between 1995 and 2010. This study analyzed the influence of five job characteristics on the meaning of work and intention to stay in the company for Generation Z using a mixed-methods approach. The analysis was conducted using SEM PLS through SmartPLS 4.0. The results indicated that Generation Z in Makassar has a unique view of the meaning of work that focuses on self-development, work-life balance, social contribution, and personal value alignment. Digitalization, pandemic experiences, social media, and local economic conditions influence their views. Generation Z expects flexibility, innovation, competitive salaries and a supportive work environment. Internal factors such as personality, life experiences, intrinsic motivation, expectations, and mental health play a dominant role. External factors such as interpersonal relationships, challenges, and organizational culture influence their perceptions of meaningful work. This research provides new insights into Generation Z’s unique views on work which are influenced by internal and external factors and the job characteristics they consider important such as self-development and work-life balance.